Motivation and Interest in Learning in Online Learning during the Covid-19 Pandemic in Yapis 02 Elementary School Manokwari - Zahra, Siti Fatimahtun; Mubarok, Zaki; Darmawan, Syamsul (Budapest International Research and Critics University, 2021)
This study aims to determine the motivation and interest in learning in online learning during the Covid-19 pandemic in students of SD Yapis 02 Manokwari. The research method used is descriptive qualitative research method because the problem is not clear, complex and dynamic and full of meaning, so qualitative data is more appropriate to use. The instrument in this research is the researcher himself. Data collection techniques by means of observation, in-depth interviews, and documentation. In the interview, the participants who will be involved are students of SD Yapis 02 Manokwari along with their parents, teachers, all of whom were selected based on certain criteria (purposive and snowball sampling). The student criteria include grade 4, 5 and 6 students who since the beginning of the pandemic have participated in online learning, with the consideration that they have understood the context of the questions asked in the interview. In addition to these criteria, students are also selected based on the ability to describe their thoughts and opinions. Data analysis techniques are carried out in line with the data collection process, carried out interactively through data reduction, data display, and verification. To maintain the credibility of the data, it is necessary to extend observations, increase persistence in research, triangulate sources, place and time, analyze negative cases and use reference materials.